Rare diseases : challenges and opportunities for social entrepreneurs - Sireau, Nicolas, 1973- (Greenleaf Publishing, 2013)
There are 7,000 rare diseases affecting 6% - 8% of the global population. That's 3.5 million people in the UK alone. Yet only 200 rare diseases have approved treatments. In recent years, there has been a surge of interest from business and social entrepreneurs in the field of health - including looking at ways to treat rare disease patients better and faster. This book presents some of the latest developments in the world of rare disease entrepreneurship from a global group of experts. It examines the topic from the business angle, considering the drug development process and providing case studies of successful orphan drug enterprises. It also looks at rare diseases from the perspective of the patient, analysing the growing rare disease patient movement, a successful patient group that uses social enterprise techniques, and chapters on key requirements for helping patients with rare diseases through registries and centres of excellence. The book will be an essential toolkit for social and business entrepreneurs who are interested in the world of rare/orphan diseases. It has the rigour of an academic publication, along with the clarity of a lay publication. An original and timely book, Rare Diseases will help to add knowledge and awareness to a vastly under-published subject.